Integrating Metadata Harvesting with Semantic Search - Dicheva, Darina; Dichev, Christo; Valtchev, Petko (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 01, 2008)
This paper presents an approach to increasing the reusability of online course repositories by collecting and annotating learning content using consensually agreed vocabularies. It proposes support to courseware authors focused on two aspects: (i) providing means for creating ontological structures (to be used as a skeleton for structuring course related material) and partially populate them with learning resources; (ii) assisting authors in selecting names for new concepts/topics combined with their subject identification. The proposed approach is implemented in an authoring tool extending the TM4L Editor.